Divergent Effects of Budgeting for Gifts versus Personal Purchases - Choe, Yuna; Kan, Christina; Polman, Evan (Journal of Consumer Research, 2023)
Abstract Consumers often set budgets with the goal to minimize their spending. Contrary to this traditional interpretation, our research suggests that budgets can take on a different psychological meaning depending on whether the budget is for a personal or gift purchase. Across 11 studies, we find that consumers aim to spend below their budgets for personal purchases (budget minimizing) but aim to spend the entirety of their budgets for gift purchases (budget maximizing). We differentiate budget maximizing from spending maximizing, showing that gift purchasers are more likely to prefer “at-budget” than “above-budget” purchases. We also show that gift purchasers have weaker savings goals than personal purchasers—a difference that mediates the effect on their budget-minimizing and -maximizing tendencies. We explore multiple reasons that could explain why savings goals are less prevalent among gift purchasers and find an upstream role for price consciousness, guilt, and perceived specialness. Finally, we find that consumers’ preference for spending the entirety of their budgets on gifts was moderated by two separate factors: consumers’ budget slack and salience. Our research adds to the literatures on mental budgeting, gift giving, and self-other decisions.